2015
DOI: 10.1186/s12990-015-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Types of Skin Afferent Fibers and Spinal Opioid Receptors that Contribute to Touch-Induced Inhibition of Heart Rate Changes Evoked by Noxious Cutaneous Heat Stimulation

Abstract: BackgroundIn anesthetized rats and conscious humans, a gentle touch using a soft disc covered with microcones (with a texture similar to that of a finger), but not with a flat disc, inhibits nociceptive somatocardiac reflexes. Such an inhibitory effect is most reliably evoked when touch is applied to the skin ipsilateral and closest to nociceptive inputs. However, the mechanism of this inhibition is not completely elucidated. We aimed to clarify the types of cutaneous afferent fibers and spinal opioid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…There are direct symmetric synaptic connections between endomorphin 2-containing primary afferent terminals and μ-opioid receptor-expressing neurons in the parasympathetic nucleus [ 34 ]. Our recent study also suggested that spinal μ-opioids are involved in the segmental inhibitory mechanism in which noxious heat stimuli-induced cardiac reflexes are inhibited by gentle skin touch [ 35 ]. Such an endogenous opioid system in the sacral cord would inhibit the ascending and/or descending limb of the micturition reflex pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There are direct symmetric synaptic connections between endomorphin 2-containing primary afferent terminals and μ-opioid receptor-expressing neurons in the parasympathetic nucleus [ 34 ]. Our recent study also suggested that spinal μ-opioids are involved in the segmental inhibitory mechanism in which noxious heat stimuli-induced cardiac reflexes are inhibited by gentle skin touch [ 35 ]. Such an endogenous opioid system in the sacral cord would inhibit the ascending and/or descending limb of the micturition reflex pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Natural stimulation such as gentle touch is able to activate these non‐noxious nerve fibers without noxious fiber activation. While little is known about the physiological functions of low‐threshold mechanoreceptive Aδ and C fibers, we found that these afferents may contribute to autonomic regulation (Hotta et al, , , ; Watanabe et al, , ). In the following section, the effects of natural stimulation (gentle stimulation) on urinary bladder function are introduced.…”
Section: Effects Of Somatic Electrical Stimulation On the Micturitionmentioning
confidence: 99%
“…Dynamic touch may reduce stress and pain more effectively than static touch Proximity to nociceptive input Ascending inhibition of pain signals at the neural gate in the spinal cord. Inhibition (2015), Melzack and Wall (1965), Watanabe, Piché, and Hotta (2015) Reduced pain signalling to the brain, inhibition of somatocardiac reflexes…”
Section: Emergent Processesmentioning
confidence: 99%